Sintesis Khalkon dan Uji Aktivitas Tabir Surya Secara In Vitro - Dewi Darmiyani Napu (Indonesian Journal of Pharmaceutical Education, 2022)
Synthesis of 2’,4’-dihydroxy-3,4-dimethoxychalcone and in vitro test of its sunscreen activity have been carried out. Chalcone was synthesized from 3,4-dimethoxybenzaldehyde and 2,4-dihydroxyacetophenone through Claisen-Schmidt condensation. The synthesis was performed by using KOH 40% under stirring at room temperature for 48 h. The synthesized compounds was characterized using FTIR, GC-MS and 1H NMR spectrometers. Further, the chalcone were screened for its in vitro sunscreen activity by using UV-Vis spectrophotometer. The result showed that the chalcone has been succesfully synthesized in 36.94% Yield. The activity of invitro test showed the chalcone has SPF values with maximal protection category at the consentration 15 µ/mL produce SPF 9.749